Altered hippocampal functional connectivity after the rupture of anterior communicating artery aneurysm - Chen, Fuxiang; Cai, Jiawei; Dai, Linsun; Lin, Yuanxiang; Yu, Lianghong; Lin, Zhangya; Kang, Yaqing; Yu, Ting; Wang, Dengliang; Kang, Dezhi (Frontiers in Aging Neuroscience, 2022)
Background and purpose: Aneurysmal subarachnoid hemorrhage predisposes to hippocampal injury, a major cause of follow-up cognitive impairment. Our previous work revealed abnormal resting-state brain network in patients after ruptured anterior communicating artery (ACoA) aneurysm. However, the functional connectivity (FC) characteristics of hippocampus and its relationship with cognitive performance in these patients remain unknown. Methods: This study ultimately included 26 patients and 19 age- and sex-matched controls who completed quality control for resting-state functional magnetic resonance imaging. The mean time series for each side of hippocampus was extracted from individuals and then a seed-to-voxel analysis was performed. We compared the difference of FC strength between two groups, and subsequently analyzed the correlations between abnormal FC and their cognitive performance. Results: The results of bilateral hippocampus-based FC analysis were largely consistent. Compared with the healthy controls, patients after the rupture of ACoA aneurysm exhibited significant decreased FC between the hippocampus and other brain structures within Papez circuit, including bilateral anterior and middle cingulate cortex, bilateral medial superior frontal gyrus, and left inferior temporal gyrus. Instead, increased FC between hippocampus and bilateral insula was observed. Correlation analyses showed that more subjective memory complains, or lower total cognitive scores were associated with decreased connectivity in the hippocampus and several brain regions such as left anterior cingulate cortex and frontotemporal cortex. Conclusion: These results extend our previous findings and suggest that patients with ruptured ACoA aneurysm exist hypoconnectivity between the hippocampus and multiple brain regions within the Papez circuit. Deactivation of the Papez circuit may be a crucial neural mechanism related to cognitive deficits in patients after rupture of ACoA aneurysm.